2022
DOI: 10.3390/jpm12040572
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm Control Better Prevents Dementia than Rate Control Strategies in Patients with Atrial Fibrillation—A Nationwide Cohort Study

Abstract: Background: Atrial fibrillation (AF) increases the risk of dementia. Whether the pharmacological rhythm control of AF can reduce the risk of dementia compared to the rate control strategy remains unclear. We hypothesize that the rhythm control strategy is better than the rate control strategy in preventing dementia. Methods: AF patients aged ≥65 years were identified from the Taiwan National Health Insurance Database. Patients receiving anti-arrhythmic drugs at a cumulative defined daily dose (cDDD) of >30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Furthermore, it has been argued that the followup periods for these studies may have been too short. In a study by Lin et al, atrial fibrillation patients receiving anti-arrhythmic drugs were found to have lower rates of dementia compared with patients receiving rate control therapy over a 4.86 ± 3.38-year follow-up period [71]. This finding confirmed the results of a study by Damanti et al, which assessed cognitive performance using the Short Blessed Test in patients treated with rhythm and rate control therapy.…”
Section: Pharmacological Rhythm Control Therapysupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, it has been argued that the followup periods for these studies may have been too short. In a study by Lin et al, atrial fibrillation patients receiving anti-arrhythmic drugs were found to have lower rates of dementia compared with patients receiving rate control therapy over a 4.86 ± 3.38-year follow-up period [71]. This finding confirmed the results of a study by Damanti et al, which assessed cognitive performance using the Short Blessed Test in patients treated with rhythm and rate control therapy.…”
Section: Pharmacological Rhythm Control Therapysupporting
confidence: 59%
“…It is consequently feasible to speculate that rhythm control therapy could cause cerebral emboli which could adversely affect cognitive outcomes. Studies have therefore been performed to attempt to determine the impact of catheter ablation [56][57][58][59][60][61][62][63], cardioversion [64][65][66][67][68], and pharmacological rhythm control therapy [69][70][71] on atrial fibrillation-associated cognitive decline.…”
Section: Rhythm Controlmentioning
confidence: 99%
“…Basic research has shown that VKAs may be related to human cognitive function and can act on the central nervous system. [31] Vitamin K participates in brain function by regulating the synthesis of [23] USA 2018 RCS AF 67 (13), 67 (13) 392711/235626/157085 Warfarin/NOAC 72 months Dementia Laurie G. Jacobs [24] USA 2009 RCS AF 82 106/26/80 Warfarin/Aspirin 12 months Dementia Victoria Jacobs [25] USA 2016 RCS AF 73.5 ± 9.6, 71.2 ± 11.9 5254/3100/2154 Warfarin/NOAC 54 months Dementia Jiunn-Cherng Lin [26]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effects of antiarrhythmic drugs on reducing the risk of death in dementia patients with a history of AF remain unclear. However, prior studies have shown that controlling cardiac rhythm (including medications for rhythm control and AF ablation) may be useful to reduce the risk of dementia in patients with AF ( 7 , 47 , 48 ). In the current study, we reported that the uses of anti-arrhythmic drugs may have potential benefits in dementia patients with a history of AF.…”
Section: Discussionmentioning
confidence: 99%